Southwest as the new internal migration destination in Turkey - Ali T. Akarca; Aysit Tansel (Institute for the Study of Labor (IZA), 2012)
Antalya and Muğla provinces located in southwestern Turkey have emerged as the new magnets for internal migration in the country. Characteristics of immigration from other provinces to these two are described, and analyzed in the context of the gravity model. The factors that affect the migration to Antalya and Muğla seem to be the same and their effects on the flows to each destination differ only slightly. Better job opportunities, especially in the hotel and restaurant services sector, appear as the main attraction fueling this migration. Surprisingly, the pleasant climates of the two provinces do not seem to matter.
Keywords: J61; R23; 330; internal migration; gravity model; Turkey; Antalya; Muğla; Binnenwanderung; Gravitationsmodell; Türkei; Arbeitsmarkt; Antalya (Provinz); Mugla (Provinz)